Prognostic value of an immunohistochemical signature in patients with esophageal squamous cell carcinoma undergoing radical esophagectomy. Issue 2 (6th January 2018) - Meng, Jin; Zhang, Junhua; Xiu, Yingjie; Jin, Yan; Xiang, Jiaqing; Nie, Yongzhan; Fu, Shen; Zhao, Kuaile
Abstract : Here, we aimed to identify an immunohistochemical (IHC)‐based classifier as a prognostic factor in patients with esophageal squamous cell carcinoma (ESCC). A cohort of 235 patients with ESCC undergoing radical esophagectomy (with complete clinical and pathological information) were enrolled in the study. Using the least absolute shrinkage and selection operator (LASSO) regression model, we extracted six IHC features associated with progression‐free survival (PFS) and then built a classifier in the discovery cohort ( n = 141). The prognostic value of this classifier was further confirmed in the validation cohort ( n = 94). Additionally, we developed a nomogram integrating the IHC‐based classifier to predict the PFS. We used the IHC‐based classifier to stratify patients into high‐ and low‐risk groups. In the discovery cohort, 5‐year PFS was 22.4% (95% CI: 0.14–0.36) for the high‐risk group and 43.3% (95% CI: 0.32–0.58) for the low‐risk group ( P = 0.00064), and in the validation cohort, 5‐year PFS was 20.58% (95% CI: 0.12–0.36) for the high‐risk group and 36.43% (95% CI: 0.22–0.60) for the low‐risk group ( P = 0.0082). Multivariable analysis demonstrated that the IHC‐based classifier was an independent prognostic factor for predicting PFS of patients with ESCC. We further developed a nomogram integrating the IHC‐based classifier and clinicopathological risk factors (gender, American Joint Committee on Cancer staging, and vascular invasion status) to predict the 3‐ and 5‐year PFS. The performance of the nomogram was evaluated and proved to be clinically useful. Our 6‐IHC marker‐based classifier is a reliable prognostic tool to facilitate the individual management of patients with ESCC after radical esophagectomy. Abstract : Immunohistochemical (IHC) assay is the most widely applied pathological technique in determining the expression of tumor‐associated proteins. Our study identifies an IHC‐based classifier as a prognostic factor for patients with esophageal squamous cell carcinoma (ESCC) after esophagectomy. We then developed an IHC marker‐based nomogram to estimate 3‐ and 5‐year progression‐free survival among patients with ESCC.